Chemodynamics of Star-Forming Regions - Hägele, Guillermo Federico (2016)
The large number of massive stars belonging to regions with violent star formation dominates the morphology of the gas, the evolution of the different generations of stars and the physical conditions of their surrounding gaseous nebulae through the photoionization of the gas, strong stellar winds, super-bubble formation and material flows. The analysis of these processes between a starburst and its environment requires the complete study of the gaseous component, from its kinematical structure to its physical properties. Using different observational techniques, low-inter mediate and high-spectral resolution spectroscopy, the physical conditions (electron density and temperatures), ionic and total chemical abundances of several atoms, reddening and ionization, structure, for the global flux and for the different kinematical components can be derive. Applying the direct method or empirical relationships for abundance determination, wc are able to perform a comparative analysis between different star-forming regions belonging to the same galaxy. The relative abundances of N/O, S/O, Ne/O and Ar/O for the different kinematical components give us clues for a common or very similar chemical evolution for the different kinematical components of each knot. It could also be indicative that the different kinematical components are different phases of the same gas. Similarities between the ionization structure of the different kinematical components could imply that the effective temperatures of the ionizing radiation fields are very similar for all the components, in spite of some small differences in the ionization state of different elements. The ionizing star clusters that excite the gas associated, to each star-forming knot that produces the different kinematical components could therefore be the same.